PrEP stigma among current and non-current PrEP users in Thailand: A comparison between hospital and key population-led health service settings - Sineenart Chautrakarn; Ajaree Rayanakorn; Kannikar Intawong; Chonlisa Chariyalertsak; Porntip Khemngern; Scott Stonington; Suwat Chariyalertsak (Frontiers Media S.A., 2022)
BackgroundPre-exposure prophylaxis (PrEP) has demonstrated effectiveness in high-risk populations. PrEP service in Thailand became free of charge under the Universal Health Coverage (UHC) in 2021. The National Health Security Office launched a pilot project in 2020 to ensure sustainable service delivery, and the national monitoring and evaluation (M&E) framework was adopted to evaluate early phase implementation. We carried out a cross-sectional survey as part of the M&E process to investigate PrEP stigma among current and non-current PrEP users from both hospital and Key Population Led Health Services (KPLHS) settings in Thailand.MethodsBetween August and October 2020, an online cross-sectional survey was conducted. A link for a self-administered questionnaire was distributed to all active PrEP centers and PrEP clients were then recruited by PrEP providers. Descriptive and univariate analysis using Chi-square were applied in the analyses. Attitudes toward PrEP were ranked from the most negative to the most positive. The negative attitude can be interpreted as PrEP stigma.ResultsThis study included 513 PrEP clients (355 from hospitals and 158 from KPLHS). In both settings, respondents' attitudes toward PrEP were generally positive, but some potential stigma was observed. 31.8% of hospital PrEP clients and 9.5% of KPLHS clients agreed that PrEP users should keep their pills hidden from others. Almost half (44.5%) of hospital clients and 18.4% of KPLHS clients agreed that PrEP users are often viewed negatively by society. More than 20% of hospital clients and 12% of KPLHS agreed that PrEP users frequently experience difficulties when their partner/lover/family find out that he or she is on PrEP. Respondents from the hospitals had slightly higher PrEP stigma than those from KPLHS.ConclusionsAccording to our findings, at the policy level, the campaign to provide PrEP education to all groups of people should be continued in order to promote a positive view of PrEP and reduce PrEP-related stigma among the general population, which is critical for successful PrEP implementation.